Esophageal Balloon-Directed Ventilator Management for Postpneumonectomy Acute Respiratory Distress Syndrome - Eric Sy; Jagadish Rao; Sherma Zacharias; Juan J. Ronco; James S. Lee (Case Reports in Critical Care)
Objective. Postpneumonectomy patients may develop acute respiratory distress syndrome (ARDS). There is a paucity of data regarding the optimal management of mechanical ventilation for postpneumonectomy patients. Esophageal balloon pressure monitoring has been used in traditional ARDS patients to set positive end-expiratory pressure (PEEP) and minimize transpulmonary driving pressure (ΔPL), but its clinical use has not been previously described nor validated in postpneumonectomy patients. The primary objective of this report was to describe the potential clinical application of esophageal pressure monitoring to manage the postpneumonectomy patient with ARDS. Design. Case report. Setting. Surgical intensive care unit (ICU) of a university-affiliated teaching hospital. Patient. A 28-year-old patient was involved in a motor vehicle collision, with a right main bronchus injury, that required a right-sided pneumonectomy to stabilize his condition. In the perioperative phase, they subsequently developed ventilator-associated pneumonia, significant cumulative positive fluid balance, and ARDS. Interventions. Prone positioning and neuromuscular blockade were initiated. An esophageal balloon was inserted to direct ventilator management. Measurements and Main Results. VT was kept around 3.6 mL/kg PBW, ΔPL at ≤14 cm H2O, and plateau pressure at ≤30 cm H2O. Lung compliance was measured to be 37 mL/cm H2O. PEEP was optimized to maintain end-inspiratory transpulmonary pressure PL<15 cm H2O, and end-expiratory PL between 0 and 5 cm H2O. The maximal ΔPL was measured to be 11 cm H2O during the care of this patient. The patient improved with esophageal balloon-directed ventilator management and was eventually liberated from mechanical ventilation. Conclusions. The optimal targets for VT remain unknown in the postpneumonectomy patient. However, postpneumonectomy patients with ARDS may potentially benefit from very low VT and optimization of PEEP. We demonstrate the application of esophageal balloon pressure monitoring that clinicians could potentially use to limit injurious ventilation and improve outcomes in postpneumonectomy patients with ARDS. However, esophageal balloon pressure monitoring has not been extensively validated in this patient population.